(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aimed to identify the impact of human resources management on the change in job stability among the millennial generation in the Kingdom of Saudi Arabia. The study was based on the suitability of the descriptive (analytical) approach to the nature of its objectives and hypotheses, where a questionnaire was distributed (electronically) containing (15) statements as a tool for collecting data. The study community consisted of (120) male and female employees. To achieve the objectives of the study, the study sample was selected using a simple random sample method from workers from the millennial generation. The data were statistically processed using the Statistical Package for Social Sciences (SPSS) program. The study reached several results, namely: There is a statistically significant effect of the role of training programs in human resources management and its impact on the change in job stability among the millennial generation in the Kingdom of Saudi Arabia. The study concluded with a set of recommendations, the most important of which were: Using accurate methods to identify the feelings of workers and their satisfaction towards work in order to increase job stability. The necessity of understanding the needs of any workers and employees in the millennial generation in the Kingdom of Saudi Arabia